NILAI TAMBAH EKONOMI TERHADAP PERTUMBUHAN LABA PERUSAHAAN BARANG KONSUMSI TAHUN 2018-2022 - Isra Herdina Fauziah Putri; Noor Syaifudin; Andi Harmoko Arifin (JURNAL LENTERA BISNIS, 2025)
Financial ratios have weaknesses in assessing financial performance where good profit growth may not reflect good performance. Economic Value Added (EVA) is one of the relevant indicators in assessing financial performance. A good EVA indicates that the company is able to generate profits exceeding the cost of capital, so it can create added value for investors. The aim of this research is to examine the relationship between EVA and profit growth in consumer goods companies. The 57 selected companies have comprehensive financial reports for the period 2018 to 2022. The analysis was carried out using a quantitative descriptive approach to identify the influence between variables. The method used is linear regression using EViews software. Based on research findings, in terms of increasing profits, EVA has a positive but not significant effect. The coefficient of determination obtained is 3.34%, indicating that 3.34% of  profit growth, can be explained by EVA. Meanwhile, profit growth of 96.66% was influenced by other factors. Companies and investors can consider the EVA value in making decisions and measuring the success of the company's future financial performance and maximizing profits.